Dynamic mode decomposition to classify cavitating flow regimes induced by thermodynamic effects. (1st September 2022) - Ge, Mingming; Manikkam, Pratulya; Ghossein, Joe; Kumar Subramanian, Roshan; Coutier-Delgosha, Olivier; Zhang, Guangjian
Abstract: The effect of temperature on the intensity and the dynamics of cavitation is investigated. Experiments of cavitating flows are conducted at various cavitation numbers and temperatures, leading to different cavity intensities and dynamic behaviors. The thermodynamic effects significantly influence the cavitation extent at elevated temperatures (over 58 °C) in water. Three regimes of instability, i.e. the sheet cavitation, the periodic single-cloud cavitation, and the aperiodic multi-clouds cavitation are distinguished based on their temporal-spatial evolutions. Application of DMD and POD decompositions on the velocity fields and gray level snapshots to determine the coherent structures and the various mechanics causing different shedding behaviors are discussed. The coherent structures obtained in cloud cavitation consist of the re-entrant jet and counter-rotating vortex structures, which are more aggressive dynamic behavior and are absent in the sheet cavitation. To inhibit the effects of hydrodynamic cavitation, it is recommended that a temperature range (55 °C–60 °C) of water be avoided in practical applications. Since working under this temperature range has larger potentials of transforming the steady sheet cavitation to unsteady cloud cavitation with the larger cavitation extent and the vigorous vapor cloud shedding. Highlights: Efficiency of machinery with cavitation can be improved by adjusting temperature. HC phenomenon is highly affected by thermal delays, σ number and Re number. . Cavitation intensity peaks and shedding regimes transition happens at 58 °C. Data analysis predicts larger dynamical structures in cloud cavitation process.